The Sustainability of Agro-Food and Natural Resource Systems in the Mediterranean Basin - Vastola, Antonella; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is focused on the challenges to implement sustainability in diverse contexts such as agribusiness, natural resource systems and new technologies. The experiences made by the researchers of the School of Agricultural, Forestry, Food and Environmental Science (SAFE) of the University of Basilicata offer a wide and multidisciplinary approach to the identification and testing of different solutions tailored to the economic, social and environmental characteristics of the region and the surrounding areas. Basilicata$1 (Bs productive system is mainly based on activities related to the agricultural sector and exploitation of natural resources but it has seen, in recent years, an industrial development driven by the discovery of oil fields. SAFE research took up the challenge posed by market competition to create value through the sustainable use of renewable and non-renewable resources of the territory. Moreover, due to its unique geographical position in the middle ofthe Mediterranean basin, Basilicata is an excellent (3z(Bopen sky(3y (Blaboratory for testing sustainable solutions adaptable to other Mediterranean areas. This collection of multidisciplinary case studies and research experiences from SAFE researchers and their scientific partners is a stimulating contribution to the debate on the development of sustainable techniques, methods and applications for the Mediterranean regions.s
Part I : Agro-Food Systems -- Food Security in the Southern Mediterranean/North Africa -- Sustainability in cereal crop production in Mediterranean environments -- Innovative crop productions for healthy foods: the case of Chia -- The hidden costs of livestock environmental sustainability: the case of Podolian cattle -- Feeding, nutrition and sustainability in dairy enterprises: the case of Mediterranean buffaloes (bubalus bubalis) -- Sustainability of sheep and goat production systems -- The role of local sheep and goat breeds and their products as a tool for sustainability and safeguard of the Mediterranean environment -- Innovative use of jenny milk from sustainable rearing -- Sustainable agricultural practices in disease defence of traditional crops in Southern Italy: the case study of tomato cherry protected by Trichoderma harzianum T-22 against Cucumber mosaic virus -- Development of integrated disease control measures for the valorisation of traditional crops in Southern Italy: the case study of "Fagiolo di Sarconi" -- Fostering sustainable climate change adaptations: a case study of the Turkish Cypriot Community$1 (Bs adoption of pomegranate farming -- The role of women in the sustainability of the wine industry through the analysis of case studies -- Part II : Natural Resource Systems and Environment -- The effects of climate change on the multifunctional role of Basilicata$1 (Bs forests: the effects induced on yield and CO2 absorption -- Wildlife agriculture interactions, spatial analysis and trade-off between environmental sustainability and risk of economic damage -- The sustainability of non-renewable resources use at regional level: a case study on allocation of oil royalties -- Land use sector involvement in mitigation policies across carbon markets -- Evaluating the role of soil variability on potential groundwater pollution and recharge in a Mediterranean agricultural watershed -- Grazing and biodiversity conservation: highlights on a Nature 2000 network site -- Evaluation of native grasses for sustainable turfgrass in the bioclimatic Mediterranean Region.-Biodiversity of hypogeous fungi in Basilicata -- Part III: New technologies -- New technologies for the sustainable management and planning of rural land and environment -- Processing plants and technologies for a sustainable Mediterranean food chain -- Geophysical techniques for plant, soil and root research related to Satellite technologies to support the sustainability of agricultural production -- Electrolyzed water in the food industry as supporting of environmental sustainability.s
Keywords: Agriculture; Food science; Environment; Agriculture; Food Science; Environmental Sciences